Do we need to vaccinate every child against COVID-19: What evidence suggests—A systematic review of opinions - Paul, Sourabh; Mishra, Chandra Mauli (Frontiers in Public Health, 2022)
Whether all children should be vaccinated against COVID-19 remains an ongoing discussion. The relatively mild cases and low risk of COVID- 19 in children compared to adults, and uncertainty about the relative harms from vaccination and disease, signifies that the balance of risk and benefit of vaccination in children is more complex. Increasing awareness of the possible rare complica¬tions of COVID-19 in children, such as Multisystem Inflammatory Syndrome in Children (MIS-C), and the “long COVID” syndrome prompted the scientific study and comparison of the risks of disease vs the safety of vac¬cination, even among the very young. Some of the key arguments for vaccinating healthy children are to achieve herd immunity and protect them from long-term consequences. Other considerations include reducing community transmission, vaccination of high risk children, school closures, vaccine supply, cost-benefit ratio, risk-benefit ratio, ethical problems and the duration of protection. The emergence of new variants of concern which may led to increased transmission of SARS-CoV-2, necessitates continual re-evaluation of the risks and benefits. The clinical trials did not address long-term effects that, if serious, would be borne by children for potentially decades. In this systemic review, we are trying to outline the points regarding for or against vaccination of children against COVID-19 with latest epidemiological evidence, to consider and highlight the complexity of policy decisions on COVID- 19 vaccination in children.